Home for the holidays - Rajski, Peggy; Foster, Jodie; Richter, W. D.; Hunter, Holly, 1958-; Downey, Robert, 1965-; Bancroft, Anne, 1931-2005.; McDermott, Dylan; Chaplin, Geraldine, 1944-; Guttenberg, Steve, 1958-; Danes, Claire, 1979-; Stevenson, Cynthia, 1962-; Durning, Charles, 1923-; et al. ([United States] : MGM Home Entertainment, 2001)
Claudia Larson is a divorced single mom who just lost her job and now has to fly home for the traditional family Thanksgiving in Baltimore. From the plane, she calls for reinforcements--and her brother Tommy makes it down from Boston with a little surprise: a handsome friend named Leo. Between dropping the turkey in their sister's lap and a few fist fights on the front lawn, Claudia and Tommy recapture their childhood and Claudia and Leo explore the sweet possibility of romance.
Information from pre-release promotional materials; release date: Sept. 4, 2001.
Originally produced as a motion picture in 1995.
Based on a short story by Chris Radant.
Special features: Audio commentary by director Jodie Foster; theatrical trailer.
Director of photography, Lajos Koltai ; editor, Lynzee Klingman ; music, Mark Isham.
Holly Hunter, Robert Downey, Jr., Anne Bancroft, Dylan McDermott, Geraldine Chaplin, Steve Guttenberg, Claire Danes, Cynthia Stevenson, Charles Durning.
Keywords: Adult children -- Drama; Thanksgiving Day -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired; Comedy -- Feature; Comedy films